The Audience, The Message, The Speaker - Hasling John (Mc Graw Hill, 2006)
One of the most crucial and difficult aspects of learning to speak in public is developing the capacity for clear thinking. Usually the fear of making presentations comes about as a result of speakers not really being sure of what they want to say. This book places a great deal of emphasis on helping readers to think through an issue and to organize their ideas so that the conclusions they reach are sound, well supported and logical. Also, a new feature of this edition is the chapter on visual aids, including a description of the latest high tech tools as well as instruction on how to use the more common equipment such as overhead and slide projectors. In the process, the author describes how visual aids can benefit the speaker as well as the audience. Also available are an instructor's manual (0-07-027000-7); and a computerized testbank in an IBM PC 5.25" (0-07-833730-5) and Macintosh 3.5" (0-07-833731-3) version.